Coralillos verdaderos (Serpentes: Elapidae) y coralillos falsos (Serpentes: Colubridae) de Veracruz, México - de la Torre-Loranca, Miguel A.; Aguirre-León, Gustavo; López-Luna, Marco A. (Instituto de Ecología, A.C., 2006)
Five species of coral snakes genus Micrurus, and 14 species of mimic false coral snakes of different colubrid genera ocurr in Veracruz, making encounters with false coral snakes more likely. However, positive identification by color pattern between coral snakes and their mimics is not reliable because of inter and intraspecific color variation and similarities in coloration between several species of these two snake families.